A study on the effectiveness of actions taken by government (Ministry of Domestic Trade and Consumer Affairs) in controlling pirated optical media in Malaysia / Hanani Ariffin, Marshita Mohd Khairi and Ernie Norhuda Che Mamat - Ariffin, Hanani; Mohd Khairi, Marshita; Che Mamat, Ernie Norhuda (2006)
In Malaysia, we has significant problem with piracy of copyright materials, particularly those embodied on optical media. The government has made many actions to stop the distributing and the producing of pirated optical media. The Copyright Act 1987 and the Optical Disc Act 2000 supported their actions. By conducting this research, we would like to analysis whether their action to control the pirated disc is effective or not for curing this problem including the sufficiency of the law relating in protecting this. This research also includes several recommendations in controlling pirated optical media in Malaysia. For our research, we have collected information from various articles and relate books, commentary from government department officers in our interview session to access additional material regarding this issue. By our research, we hope the aggressive action by government can decrease the number of cases as regard the pirated CDs, VCDs, and DVDs in our market. We also emphasis in creating awareness to our consumers, don't give support the piracy of optical product and also to create awareness to the parties, who produces the pirated optical disc to respect the owner of intellect property right.